The Influence of Green Chemistry Activities on Students’ Environmental Care Attitudes - Denisa Ajeng Retno Anggraeni; Moersilah Moersilah (Scientia Publica Media, 2024)
This study aims to investigate the effect of green chemistry activities on students’ environmental care attitudes. A quasi-experimental with a pretest-posttest control group design was used in this study. The participants were 44 eleventh-grade students at a public school in West Java, Indonesia. Two intact classes were randomly assigned to the control group (n=19) and the experimental group (n=25). Control group students carried out traditional experiments, while experimental group students carried out green chemistry experiments. The data obtained were analyzed using independent samples t-test and paired samples t-test. The results of the independent samples t-test (ɑ=5%) show that the p values obtained for the pretest and posttest scores are 0.189 and 0.037, respectively. In addition, the results of the paired samples t-test indicated that the p-values for the control and experimental groups were 0.349 and 0.000, respectively. This shows that there is a significant difference in the environmental care attitude score between the two groups in favor of the experimental group. The experimental group also showed a greater increase in scores than the control class after treatment. It can be concluded that green chemistry experiments and activities are effective in promoting the environmental care attitudes of eleventh-grade students on the topic of acids and bases. It is suggested to teachers use the green chemistry curriculum on other topics to improve student learning.